2017
DOI: 10.1016/j.chemosphere.2017.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual variability of soil arsenic metabolism by human gut microbiota using SHIME model

Abstract: Arsenic (As) metabolism by human gut microbiota has been evidenced with in vitro experiments from contaminated soils. In this study, the variability in the metabolic potency toward As-contaminated soils and gut microbial diversity were investigated between healthy individuals (Adult versus Child). Arsenic bioaccessibility in the colon phase increased by 1.4-6.8 and 1.2-8.7 folds for adult and child, respectively. We found a high degree of As methylation for the colon digests of the adult (mean 2 μg methylarsen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 52 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…Another study showed that 100 ppb arsenic exposure for 13 weeks changed the gut microbial composition and altered important microbial functional pathways (carbohydrate metabolism [especially pyruvate fermentation], short-chain fatty acid synthesis, and starch utilization) that could influence host metabolism (38). Moreover, child gut microbiota exhibit high levels of As III , the more toxic form of arsenic, which could result in increased health risk (39).…”
mentioning
confidence: 99%
“…Another study showed that 100 ppb arsenic exposure for 13 weeks changed the gut microbial composition and altered important microbial functional pathways (carbohydrate metabolism [especially pyruvate fermentation], short-chain fatty acid synthesis, and starch utilization) that could influence host metabolism (38). Moreover, child gut microbiota exhibit high levels of As III , the more toxic form of arsenic, which could result in increased health risk (39).…”
mentioning
confidence: 99%
“…In one instance the encoding arsM was found adjacent to an arsC , suggesting that this particular ArsM is part of an organized arsenic resistance response for a ( Para ) Bacteroides organism. ArsM functional variability would contribute to inter‐individual microbiome uniqueness (Eckburg et al ., ; O'Toole, ; Ukhanova et al ., ; Pérez‐Cobas et al ., ), which is supported by a SHIME‐based study that concluded arsenic methylation varies between individuals and particularly when comparing adults to children (Yin et al ., ). Again, however, there are caveats.…”
Section: Arsenic and The Git Microbiomementioning
confidence: 97%
“…The high variability in microbiota may suggest the diversity of the As metabolic potency among different people. A recent study confirmed that the degree of As methylation by gut bacteria from different healthy individuals was largely different [140]. Another in vitro study suggested that Fe 3+ decreased the As bioaccessibility and increased As methylation by altering the gut microbiota composition [141].…”
Section: Gut Microbiome and As Susceptibilitymentioning
confidence: 97%